2023
DOI: 10.3390/nu15030742
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Nutritional and Metabolic Outcome of Single Anastomosis Duodeno-Ileal Bypass with Sleeve Gastrectomy (SADI-S)

Abstract: Introduction: Single Anastomosis Duodenal-Ileal Bypass with Sleeve Gastrectomy (SADI-S), like other hypoabsorptive procedures, could be burdened by long-term nutritional deficiencies such as malnutrition, anemia, hypocalcemia, and hyperparathyroidism. Objectives: We aimed to report our experience in terms of mid-term (2 years) bariatric, nutritional, and metabolic results in patients who underwent SADI-S both as a primary or revisional procedure. Methods: One hundred twenty-one patients were scheduled for SADI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This was managed by extending the common limb to 250–300 cm. A two-year follow up study by Marincola et al [ 22 ] reported Vitamin D and folate nutritional deficiency post-SADI in 31.82% and 9.09% of patients, respectively. These findings underscore the importance of regular nutritional checkups on patients who undergo these revisional bariatric procedures, especially since many obese patients suffer from micronutrient deficiencies even prior to undergoing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This was managed by extending the common limb to 250–300 cm. A two-year follow up study by Marincola et al [ 22 ] reported Vitamin D and folate nutritional deficiency post-SADI in 31.82% and 9.09% of patients, respectively. These findings underscore the importance of regular nutritional checkups on patients who undergo these revisional bariatric procedures, especially since many obese patients suffer from micronutrient deficiencies even prior to undergoing bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we ascribed the shortening of hospital stay observed in BS-G as probably due to the application of enhanced recovery after surgery protocols through the years. In fact, our clinical practice has shifted from a discharge on postoperative days 3-4 to the current discharge between postoperative days 1 and 2 [12,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The Clavien-Dindo classification was utilised to assess the severity of postoperative complications [15]. The discharge and follow-up protocols have been previously described [12,[16][17][18]. Demographic and clinical data, as well as perioperative results, were obtained by a comprehensive evaluation of patient documents and electronic databases.…”
Section: Post-operative Protocolmentioning
confidence: 99%
“…The post-operative protocol has been elucidated in extenso in prior scientific studies [ 19 , 20 , 25 , 30 , 31 ]. All RYGB patients received FitForMe WLS Forte ® as vitamins and minerals supplementation customized for this bariatric procedure (see https://fitforme.it/product/wls-forte/?_gl=1*12cjjqc*_up*MQ..&gclid=CjwKCAjw1t2pBhAFEiwA_-A-NHqOIVB1CPEiVIzNVJysVEaQrxrCjX_OPjpszcp0CfFu7NwCs0mZlBoCJ20QAvD_BwE#product-tabs for details of composition).…”
Section: Methodsmentioning
confidence: 99%